Infants’ Selective Visual Attention Is Dependent on Maternal Affect and Emotional Context - Juvrud, Joshua; Haas, Sara A.; Fox, Nathan A.; Gredebäck, Gustaf (Frontiers in Psychology, 2021)
Development of selective attention during the first year of life is critical to cognitive and socio-emotional skills. It is also a period that the average child’s interactions with their mother dominates their social environment. This study examined how maternal negative affect and an emotion face prime (mother/stranger) jointly effect selective visual attention. Results from Linear Mixed-Effects modeling showed that 9-month-olds (N=70) were faster to find a visual search target after viewing a fearful face (regardless of familiarity) or their mother’s angry face. For mothers with high negative affect, infants’ attention was further impacted by fearful faces, resulting in faster search times. Face emotion interacted with mother’s negative affect, demonstrating a capacity to influence what infants attend to in their environment.